2018
DOI: 10.12659/msm.905804
|View full text |Cite
|
Sign up to set email alerts
|

Bone Cement-Augmented Short-Segment Pedicle Screw Fixation for Kümmell Disease with Spinal Canal Stenosis

Abstract: BackgroundThis study aimed to explore the feasibility and efficacy of bone cement-augmented short-segmental pedicle screw fixation in treating Kümmell disease.Material/MethodsFrom June 2012 to June 2015, 18 patients with Kümmell disease with spinal canal stenosis were enrolled in this study. Each patient was treated with bone cement-augmented short-segment fixation and posterolateral bone grafting, and posterior decompression was performed when needed. All patients were followed up for 12–36 months. We retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…There are alternative treatment strategies for stage III Kümmell disease, but consensus regarding which is most feasible and effective is lacking. For stage III patients with severe stenosis of the spinal canal and neurological symptoms, the objective of surgery is to relieve cord compression, eliminate spinal instability, and restore the sagittal balance of the spine [12,19] Many studies have suggested that the main factor contributing to delayed neurological deficits following vertebral collapse in the osteoporotic spine is instability at the fracture site, rather than mechanical compression of the spinal cord by bone fragments [25,26]. Therefore, maintaining spinal stability is important for treating stage III patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are alternative treatment strategies for stage III Kümmell disease, but consensus regarding which is most feasible and effective is lacking. For stage III patients with severe stenosis of the spinal canal and neurological symptoms, the objective of surgery is to relieve cord compression, eliminate spinal instability, and restore the sagittal balance of the spine [12,19] Many studies have suggested that the main factor contributing to delayed neurological deficits following vertebral collapse in the osteoporotic spine is instability at the fracture site, rather than mechanical compression of the spinal cord by bone fragments [25,26]. Therefore, maintaining spinal stability is important for treating stage III patients.…”
Section: Resultsmentioning
confidence: 99%
“…Various surgical strategies have been developed, including percutaneous kyphoplasty (PKP) or vertebroplasty (PVP), anterior-only, posterior-only, and combined anterior and posterior procedures [8][9][10]. For stages I and II Kümmell disease, adequate pain relief, vertebral body height restoration, and kyphosis correction are achieved with PKP and PVP [11][12]. However, stage III Kümmell disease patients with spinal canal stenosis, particularly with nerve damage, PKP or PVP are less effective, with a higher risk of cement leakage, and potential severe neurological damage.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of Kummell's disease is relatively low and nonsurgical treatments have usually been less effective. Hence, many surgeons have advised that Kummell's disease should be treated by operative intervention [8] . For the posterior vertebral wall rupture, combined with severe kyphotic deformity and neurological symptoms at stage III of Kummell's disease, open surgery is recommended [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of Kümmell's Disease With Thoracolumbar Kyphosis: A Minimal Two-Year Follow-Up Background Since Kümmell's disease was rst proposed by Hermann Kümmell in 1895,it has been gradually recognized and understood by spinal surgeons [1].With the aging of the population,Kümmell's disease,as a complication of OVCF [2][3][4][5],also shows increased incidence [6,7].At present,Kümmell's disease is de ned as ischemic necrosis of the vertebral body after minor spinal injury [5,6,8].As the disease progresses, the injured vertebra gradually collapse tend to become wedge shaped due to bone necrosis,followed by kyphosis deformity of the spine.Due to the collapse of the posterior wall of the vertebral body and instability of the injured vertebrae,some injured vertebrae are prone to secondary spinal stenosis,and lead to spinal cord compression and neurological symptoms.…”
Section: Radiographic and Clinical Outcomes Of Surgicalmentioning
confidence: 99%